Cyberlaw and COVID-19 Pandemic: A Comprehensive Scholarly Analysis - Azhar, Lucilia; Phahlevy, Rifqi Ridlo; Fiddina, Irta (Proceedings of The ICECRS, 2023)
This scholarly analysis presents a comprehensive overview of the intersection of cyberlaw and the COVID-19 pandemic. Using Lens.org and Zenodo.org, the study's objective was to enhance digital literacy skills, data management capabilities, and information retrieval proficiency among students. It encompasses a wealth of information, with 18,746 initial records. After filtering, 2,357 relevant documents were obtained. The data was then meticulously analyzed, including identifying top institutions, publishers, fields of study, active authors, citation patterns, and more. The results offer valuable insights, and the dataset has been made accessible for various stakeholders, particularly students and researchers looking to delve into the dynamic landscape of cyberlaw and its response to the pandemic. Highlight: Emerging Threats: Stay updated on cybersecurity trends to proactively address emerging threats and vulnerabilities in the digital landscape. Data Security: Protect sensitive data by understanding the latest techniques used in data breaches and how to counteract them. User Privacy: Safeguard online privacy rights and ensure compliance with data protection regulations to maintain trust with users and customers. Keywords: Cybersecurity Trends, Data Breaches, Online Privacy, Threat Detection, Network Protection